Current Situation of PC12 Cell Use in Neuronal Injury Study - Wang, Wei-Li; Dai, Rong; Yan, Han-Wen; Han, Chun-Ni; Liu, Li-Song; Duan, Xiao-Hua (International Journal of Biotechnology for Wellness Industries, 2015)
The nervous system diseases are easy to get and hard to cure. The mechanism is bound up with nervous cells injure, so it’s significant to study medicine protect nervous cells injure. We need find an ideal model to study these diseases. PC12 cell is a pheochromocytoma cell line from RattusNorvegicus, because it has some characters of nerve cells and easy to cultivate and passage, these cells have been proved to be a useful cell model to study nervous physiology and pharmacology. There are several of PC12 cells, American type culture collection supply two kinds of PC12 cell named PC12 cell and PC12Adh. There are high differentiation, low differentiation and undifferentiating in domestic. Although they are very similar, there are still some differences, and not every PC12 cell is effective for every experimental model. After compared, we hold that PC12Adh cell line is more suitable for neurite outgrowth studies under ROCK inhibitor than the PC12 cell line, PC12 cells that induced by NGF and high differentiated PC12 cell are similar to cerebral cortical neurons, they are suitable for various physiological and pathological study of nervous system. Undifferentiated PC12 cells due to low levels of dopamine, therefore it is not suitable for study on neural cells.